An integrated fuzzy multi-measurement decision-making model for selecting optimization techniques of semiconductor materials - Abdullah Hussein Abdullah Al-Amoodi (Tanjong Malim, 2024)
An integrated fuzzy multi-measurement decision-making model for selecting optimization techniques of semiconductor materials by Abdullah Hussein Abdullah Al-Amoodi